(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article analyzes the role of sociological discourse in the development of the socio-political and socio-cultural life of the country and its conceptual scientific and methodological foundations. The role and importance of sociological discourse in achieving a high level of political consciousness and worldview of citizens is enormous. The development of civil initiatives and their role in building a dialogue between the government and civil society are also considered.